Properties, evaluation and application of naringin magnetic molecularly imprinted polymer based on synergistic imprinting strategy - Zhang, Li‐Ping; Wang, Miao; Li, Tian; He, Yi‐Fan; Li, Shu‐Jing; Wang, Lan; Mao, Long‐Fei (Journal of food science, 2024)
A novel and facile surface molecularly imprinted polymer coated on magnetic chitosan (Fe3O4@CS@MIP) was fabricated for the selective recognition and enrichment of naringin (NRG). The Fe3O4@CS@MIP was prepared based on covalent–noncovalent synergistic imprinting strategies, utilizing 4‐vinyl phenyl boric acid as covalent functional monomer, deep eutectic solvent (choline chloride/methacrylic acid [ChCl/MAA]) as non‐covalent functional monomer and Fe3O4@CS nanoparticles as the magnetic support. The obtained Fe3O4@CS@MIP exhibited a uniform morphology, excellent crystallinity, outstanding magnetic properties, and high surface area. Owing to the double recognition abilities, the resultant polymer showed exceptional binding performance and rapid mass transfer in phosphate buffer (pH 7.0). The maximum binding amount of Fe3O4@CS@MIP was found to be 15.08 mg g−1, and the equilibrium adsorption could be achieved within 180 min. Moreover, they also exhibited stronger selectivity for NRG and satisfactory reusability, with only 11.0% loss after five adsorption‐desorption cycles. Additionally, the Fe3O4@CS@MIP, serving as an adsorbent, presented practical application potential in the separation and enrichment of NRG from pummelo peel, with extraction efficiency in the range of 79.53% to 84.63%. This work provided a new strategy for improving the performance of MIP and contributed an attractive option for the extraction of NRG in complex samples.